Correlation of the Anatomy of the Intersphincteric Anal Fistula with Sex: An Analysis through Anorectal Three-Dimensional Ultrasound - Graziela Olivia da Silva Fernandes; Maysa Queiroz Maciel; Rosilma Gorete Lima Barreto; Maura Tarcianny Oliveira Cajazeiras; Nikolay Coelho da Mota; Yana Pavan; Marcelo Travassos Pinto; Letícia Freitas de Aquino; João Batista Pinheiro Barreto (Journal of Coloproctology)
Introduction Anal fistula surgery is often associated with continence disorders due to transection of the anal sphincter muscles. A comprehensive understanding of the anatomy of the anal canal and fistula can help prevent this outcome.